Surzhyk as a means of pejorative assessment in the language of mass communication - Левченко, Тетяна Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article states that journalistic broadcasting is intended to create public opinion or to develop an exact attitude of society towards certain phenomena and events of internal political and international life.  The Ukrainian-Russian surzhyk is not only focused on the linguistic taste and contemporaries’ sharp speech attention, but also on the position of cognition through its affiliation with another language, Russian in particular, because of its high frequency and semantic correction in accordance with fashionable communication. In the language of mass communication at the beginning of the XXI century, surzhyk often serves for the transmission of linguistic illiteracy, the absence of the language culture of the heroes of publications, as well as to attract the attention of readers to the person, events, phenomena referred to in the text. The Ukrainian-Russian surzhyk is basically the correspondence to well-known and widely used normative words. They are presented mainly in quotations of heroes of publications. It was found out that pejorative vocabulary means lexical units, the lexical meaning of which includes the connotative aspect (negative emotional sem), which expresses the negative attitude of a speaker to an addressee. That may be often vulgar, versatile, slang vocabulary. Researchers of pejorative vocabulary in the language of the press notice that the printed media texts are full of general neutrality of the narrative tone, but in recent times the use of lexemes with a negative assessment has significantly intensified.In the language of modern mass media among surzhykisms such thematic groups are distinguished: the words of politeness, tokens on the designation of food, names of household things, items of everyday use, personal things, also surzhykisms are used in the sphere of trade between the seller and the buyer; sometimes they have an ironic coloration, and so on. We consider that the surzhyk is a kind of Ukrainian national language that arose as a result of use of words of the Ukrainian and Russian languages by the speakers; it is created out of any norms and poses a threat to the national language. Surzhik has a number of objective prerequisites, the historical character associated with the Russian factor in particular. Many years of planting the Russian language could not but affect the purity of the Ukrainian language.